2015
DOI: 10.1074/jbc.m114.619320
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Disulfide Bonding and N-Glycosylation Defines SLC4 Na+-coupled Transporter Extracellular Topography

Abstract: Background: Cysteines in extracellular loop 3 (EL-3) are highly conserved in SLC4 Na ϩ -coupled transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The two disulfide bonds are important for the folded conformation of EL3. Mutations of each of the four highly conserved cysteine residues make EL3 highly accessible to protease digestion 24 . EL3 is also located at the dimeric interface between two subunits and involved in dimerization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The two disulfide bonds are important for the folded conformation of EL3. Mutations of each of the four highly conserved cysteine residues make EL3 highly accessible to protease digestion 24 . EL3 is also located at the dimeric interface between two subunits and involved in dimerization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As N‐glycosylation and disulfide‐bond formation often occur co‐translationally, and since many proteins comprise a number of both these modifications, it is only natural that these two processes are intricately connected during folding . These connections have been elegantly explored in the Helenius laboratory using a pulse‐chase/immunoprecipitation approach in combination with 2D SDS–PAGE .…”
Section: Interplay Between N‐glycosylation and Disulfide‐bond Formationmentioning
confidence: 99%
“…It is known that N-linked glycosylation plays a major role in the proper folding and processing of glycoproteins (33,34). Specifically, N-linked glycosylation has been demonstrated to facilitate proper disulfide bond formation (35). In nearly all alphaherpesvirus gKs, there are four extracellular cysteines: three in domain 1 and one in domain 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seminal work of Hammond et al demonstrated a critical role for N-linked glycosylation in viral glycoprotein folding (48), and it has since been shown that the positioning of glycosylation sites is important for optimal protein expression (33). N-linked glycans are critical for directing proper folding of viral and cellular proteins, and proper folding is important for correct disulfide bond formation (35,45,49,50). Not surprisingly, due to the importance of glycosylation to protein processing, mutations in glycosylation have profound effects on virion assembly.…”
Section: Discussionmentioning
confidence: 99%